Use of the Digital Dictionary Jamak Taksir to Improve Arabic Writing Skills for Students of the Arabic Language Education Study Program, Darul A'mal Islamic Institute, Lampung - Joni Kawijaya; Yusuf Mustofa (Al-Kalimat: Journal of Linguistic and Arabic Teaching, 2025)
This research starts from the difficulty of Arabic language learners in mastering the plural of taxis which have irregular patterns. Early surveys showed 90% of college students had difficulty using the plural of the appraisal when writing, while 85% stated conventional dictionaries were less practical. The lack of digital learning resources that specifically discuss the plural of estimates is the main problem that this research tries to overcome. This research aims to develop an interactive web-based digital plural dictionary of taxir to improve writing skills (kitabah). Using the ADDIE method, this study involved 12 students of Arabic language education as subjects. Data were collected through tests, questionnaires, and interviews, then analyzed quantitatively descriptively. The results showed that this digital dictionary obtained a validation score of 4.3/5 from experts. The effectiveness test proved a significant increase in the average value from 57.92 (pre-test) to 81.67 (post-test) with a significance of 0.000. These findings indicate that digital dictionaries are effective in improving writing skills (kitabah). This research makes an important contribution to the development of technology-based Arabic language learning media. This research not only answers the practical needs of learners, but also opens up opportunities for innovation in Arabic language learning in the digital era. Researchers recommend further research so that there is development of additional features such as audio pronunciation and database expansion.